Supplementation of wheat flour with natural sources to reduce cholesterol and enhance quality of bakery products in Egypt and Sudan - Rabab Hashem Mohamed Mohamed; Amira Shawky Soliman; Mohamed Fathi Abolela; Mohamed Said Abbas (Cairo : Rabab Hashem Mohamed Mohamed, 2019)
As Egypt is the largest wheat importer globally, the government is aiming to find alternatives to reduce wheat imports and to cultivate reclaimed lands. Comparative studies were conducted to investigate the effect of substituting portions of wheat with quinoa, cassava and guar flours at levels of 20%, 30% and 5%, respectively, on chemical, rheological and sensory characteristics of the Egyptian balady bread. The study was carried out in the Agricultural Research Center, Egypt, and aimed to reduce the amount of wheat used in making wheat bread, a staple food in the country, and to enhance its nutritional and baking quality values , reduce cholesterol through the Functional Food (Gaur seeds- quinoa seeds and cassava roots), and production of healthy bread. Results proved that guar gave poor sensory characteristics, in addition to its insignificant substitution level (5%). Substituting wheat flour with 20% quinoa resulted in elevating protein, fat and fiber percentages than that of wheat (16.4, 2.15 and 1.01%, respectively). Bread made from quinoawheat blend gave the lowest fungal count and the highest shelf life (8 days) at room temperature about (20-25{u00B0}C), but resulted in significant changes in stability, volumes, texture, and structure.Substituting wheat with 30% cassava gave the highest carbohydrate content, didn{u2019}t change any of the rheological properties and no significant difference was noticed between wheat flour and 30% cassava-wheat bread in all sensory tests. Adding quinoa and cassava to wheat flour helped in reducing cholesterol levels in blood. Groups fed on bread supplements with 30% cassava and 20% quinoa were showed the highest decrease in total cholesterol, triglyceride levels, low-density lipoprotein (LDL) and highest increase in Highdensity lipoprotein (HDL), and also, they showed decrease in serum aspartate aminotransferase (AST) and Serum alanine aminotransferase (ALT)
Thesis (Ph.D.) - Cairo University - Faculty of African Postgraduate Studies - Department of Natural Resources
Issued also as CD
Keywords: Cassava; Guar; Quinoa